2003
DOI: 10.1046/j.1460-9568.2003.02692.x
|View full text |Cite
|
Sign up to set email alerts
|

A damage to locus coeruleus neurons converts sporadic seizures into self‐sustaining limbic status epilepticus

Abstract: Various studies demonstrated that the neurotransmitter norepinephrine (NE) plays a relevant role in modulating seizures; in particular, a powerful effect consists in delaying the kindling of limbic areas such as the amygdala and hippocampus. Given the rich NE innervation of limbic regions, we selected a sensitive trigger area, the anterior piriform cortex, to test whether previous loss of noradrenergic terminals modifies sporadic seizures in rats. The damage to locus coeruleus terminals was produced by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
59
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 37 publications
12
59
0
Order By: Relevance
“…However, in mice, 5HT loss is milder, while a severe DA depletion occurs, as described in detail by the Colado's group (Colado et al, 2001) and shown by other studies (Stone et al, 1987;Logan et al, 1988;Ali et al, 1991;Cadet et al, 1995;Fornai et al, 2001Fornai et al, , 2004b. Both monoamines might modulate seizures (see, for instance, Pasini et al, 1996;Starr, 1996;Heisler et al, 1998;Torta and Monaco, 2002;Giorgi et al, 2003Giorgi et al, , 2004. However, this is unlikely to occur in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…However, in mice, 5HT loss is milder, while a severe DA depletion occurs, as described in detail by the Colado's group (Colado et al, 2001) and shown by other studies (Stone et al, 1987;Logan et al, 1988;Ali et al, 1991;Cadet et al, 1995;Fornai et al, 2001Fornai et al, , 2004b. Both monoamines might modulate seizures (see, for instance, Pasini et al, 1996;Starr, 1996;Heisler et al, 1998;Torta and Monaco, 2002;Giorgi et al, 2003Giorgi et al, , 2004. However, this is unlikely to occur in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Limbic structures are widely innervated by LC noradrenergic fibers, and among them the olfactory cortex and hippocampus are particularly rich in NE terminals (Fallon and Moore, 1978;Giorgi et al, 2003, and the present data). In models of limbic seizures the loss of NE was shown to modulate significantly seizure incidence and susceptibility (Weinshenker and Szot, 2002;Giorgi et al, 2004).…”
Section: Discussionsupporting
confidence: 62%
“…NE fibers originating from the nucleus Locus Coeruleus (LC) innervate profusely the whole cortex, and particularly the olfactory cortex (Fallon and Moore, 1978;Giorgi et al, 2003, and the present data).…”
supporting
confidence: 62%
“…This refers to a different role of the LC activation that could lie in a feedback effect upon the higher brain structures. Indeed, it was shown that the noradrenegic projections from the LC have inhibitory influence on the kindling effect in the amygdala and the hippocampus (Giorgi et al, 2003). Beside that, the neurons in the amygdala that had been inhibited by the stimulation of the carotid sinus and baroreceptors were also inhibited by the stimulation of the LC (Schätze et al, 1987).…”
Section: Tonic and Phasic Functions Of The Brain Monoaminergic Signalmentioning
confidence: 99%